Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Kinerja Perusahaan Sebagai Moderating (Studi Empiris Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2011-2013) - Pradana, Prima Andi, Dr. Triyono, S.E., M.Si (2016)
The purpose of this study was to analyze and examine the influence of Corporate Social Responsibility (CSR) to corporate value and corporate performance as moderating variable on mining companies listed on the Stock Exchange in 2011-2013. This study uses a quantitative method using secondary data obtained from ICMD. The population in this study are all mining companies listed on the Stock Exchange in 2011-2013. The number of samples in this study as many as 85 samples. Methods of sample collection using purposive sampling techniques. The analytical tool used include normality test, multicollinearity, heteroscedasticity test, autocorrelation test, multiple linear regression, F test, test the coefficient of determination R, and t test. Based on the results of data analysis can be concluded in the first hypothesis CSR variables affect the value of the company. While the second hypothesis corporate performance as the moderating variable has no effect on between CSR and corporate value. The implication in the first hypothesis, large or small CSR practices can affect the value of the company. While the implications of the second hypothesis, CSR can not increase the value of the company at the time of high-performance enterprise and vice versa CSR can not lower the value of the company at the time of the company's performance is low.